Liftings of Nichols algebras of diagonal type I. Cartan type A - Andruskiewitsch, Nicolás; Angiono, Iván Ezequiel; García Iglesias, Agustín (2025)
Artículo finalmente publicado en: Andruskiewitsch, N., Angiono, I. E. y García Iglesias, A. (2017). Liftings of Nichols algebras of diagonal type I. Cartan type A. International Mathematics Research Notices, 2017 (9), 2793-2884. https://doi.org/10.1093/imrn/rnw103